Halide ion controlled shape dependent gold nanoparticle synthesis with tryptophan as reducing agent: enhanced fluorescent properties and white light emission - Kasture, Manasi; Sastry, Murali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2010)
We report the synthesis of Au nanoparticles in presence of two surfactants cetyltrimethyl ammonium chloride (CTAC) and cetyltrimethyl ammonium bromide (CTAB) by reducing Au(3+) ions with tryptophan. Interestingly, triangular shaped particles were seen to form in presence of CTAB, while spherical nanoparticles resulted with CTAC. The highlight of this result is the white light emission from the Au triangles obtained when CTAB is used. These results are supported by lifetime measurements and fluorescence. (C) 2009 Elsevier B. V. All rights reserved.